PENGARUH PROMOSI JABATAN DAN PENEMPATAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN LABUHANBATU - Reni Kartikaningsih (LPPM Universitas Labuhanbatu, 2020)
Job Promotion is one way of upgrading an employee from an older position to a new position, and there is an increase in salary, authority and responsibility. Job Placement is the process of assigning / filling positions or reassigning employees to new tasks / positions or different positions. Performance provides work that is done in quality and quantity achieved by an employee in carrying out tasks in accordance with responsibilities. This study uses a random sampling method with a sample of 45 employees. Simultaneous testing (F test) is determined that the value of Fcount (277.515)> Ftable (3.204) 5% alpha value is concluded simultaneously variable promotion and job placement variables have a positive and significant effect on performance variables. employees. From the results of these studies that the value of tcount for the variable promotion position is 6.156 and job placement is 6.865, that is, the significant value for each independent variable (0.000); (0,000). Meanwhile, the t-table value in the t distribution statistical table with a level of test Î± = 5% and df1 = 45 is 1.679. Based on these criteria, the value of tcount> ttable, namely (6.156 â‰¥ 1.679); (6,865> 1,679) concluded that the variable partially job promotion has a positive and significant effect on employee performance and partially job placement has a positive and significant effect on employee performance.